The great lockdown: Pandemic response policies and bank lending conditions - Carlo Altavilla; Francesca Barbiero; Miguel Boucinha; Lorenzo Burlon (European Central Bank (ECB), 2020)
This study analyses the policy measures taken in the euro area in response to the outbreak and the escalating diffusion of new coronavirus (COVID-19) pandemic. We focus on monetary, microprudential and macroprudential policies designed specifically to support bank lending conditions. For identification, we use proprietary data on participation in central bank liquidity operations, high-frequency reactions to monetary policy announcements, and confidential supervisory information on bank capital requirements. The results show that in the absence of the funding cost relief and capital relief associated with the pandemic response measures, banks' ability to supply credit would have been severely affected. The results also indicate that the coordinated intervention by monetary and prudential authorities amplified the effects of the individual measures in supporting liquidity conditions and helping to sustain the flow of credit to the private sector. Finally, we investigate the potential real effects of the joint pandemic response measures by estimating the adjustment in labour input variables for firms that in the past have been more exposed to similar policies. We find that, in absence of monetary and prudential policies, the pandemic would lead to a significantly larger decline in firms' employment.
Keywords: E51; E52; E58; G01; G21; G28; 330; COVID-19 crisis; monetary policy; bank lending; prudential policy